2009
DOI: 10.1002/9780470584002.ch4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strength of CTP Triplex SiC Fuel Clad Tubes After Irradiation in MIT Research Reactor Under PWR Coolant Conditions

Abstract: An experiment was conducted in the MIT Research Reactor (MITR) to irradiate triplex silicon carbide fuel cladding tubes under typical Pressurized Water Reactor conditions. Measurements were made to determine the impact of exposure on strength and swelling. The SiC clad tubes were fabricated by Ceramic Tubular Products (CTP) with dimensions typical of 15 x 15 commercial PWR reactor fuel. The triplex tubes contain 3 layers, an inner monolithic SiC layer to maintain hermeticity, a central SiC/SiC composite layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…One of the SiC cladding concepts has the form of a triplex composite tube, consisting of a chemically vapor deposited (CVD) SiC inner layer, SiC fiber-reinforced SiC matrix (SiC f /SiC) composite layer, and another CVD SiC outer layer for corrosion protection [13,14]. SiC ceramics show outstanding oxidation resistance and a low hydrogen liberation rate in hot steam, compared with the current Zr alloys.…”
Section: Introductionmentioning
confidence: 99%
“…One of the SiC cladding concepts has the form of a triplex composite tube, consisting of a chemically vapor deposited (CVD) SiC inner layer, SiC fiber-reinforced SiC matrix (SiC f /SiC) composite layer, and another CVD SiC outer layer for corrosion protection [13,14]. SiC ceramics show outstanding oxidation resistance and a low hydrogen liberation rate in hot steam, compared with the current Zr alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, SiC has been used under high temperature conditions such as in fusion reactors and other very high temperature reactors due to its excellent properties at high temperatures. In addition, SiC monoliths and SiC/SiC composites have been investigated for use in LWRs (Carpenter, 2006;Feinroth et al, 2009;Jung et al, 2012;Kim et al, 2012). According to Feinroth et al (2009), triplex specimens have the same hoop strength as unirradiated samples within 2 standard deviations after exposure to typical PWR operating conditions, including fast neutron irradiation.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, SiC monoliths and SiC/SiC composites have been investigated for use in LWRs (Carpenter, 2006;Feinroth et al, 2009;Jung et al, 2012;Kim et al, 2012). According to Feinroth et al (2009), triplex specimens have the same hoop strength as unirradiated samples within 2 standard deviations after exposure to typical PWR operating conditions, including fast neutron irradiation. Furthermore, their study showed that the addition of an outer composite layer with a unique fiber architecture and an outer environmental barrier layer can provide additional pressure retention capacity.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4]. In view of the most serious damage and large amount of radioactive release caused by hydrogen explosion in Fukushima nuclear power plant accident in Japan, SiC ceramic matrix fuel cladding materials can reduce the risk of hydrogen production by several thousand times, and provide similar protection for nuclear fuel with zirconium alloy, indicating that SiC ceramic also have advanced application potential in the field of nuclear energy, which was tested by professor Kazimi team from Massachusetts Institute of Technology (MIT) [5,6]. However, it is difficult to make SiC ceramic parts with a large and complex shape because of its intrinsic brittleness and poor processability.…”
Section: Introductionmentioning
confidence: 99%